Syarat Melakukan Poligami Menurut Hadits Abu Dawud dan Pasal 5 UU No. 1 Tahun 1974 (International Forum of Researchers and Lecturers, 2025)
This study will discuss the requirements for polygamy according to the Hadith of Abu Dawud and Article 5 paragraph (1) of Law No. 1 of 1974 concerning Marriage. This research employs a descriptive-analytical method with a normative legal approach, aiming to obtain an in-depth understanding and interpretation of the meaning of an applicable legal norm. The sources of data for this research include statutory regulations, particularly Law No. 1 of 1974 concerning Marriage, and the Hadith collection of Abu Dawud as a source of Islamic teachings. If a husband wishes to have more than one wife, he must submit an application for permission to practice polygamy to the court in his local jurisdiction. Subsequently, if permission is granted by the court, polygamy may still only be carried out under certain conditions, such as the consent of the first wife and assurance that the husband can guarantee the welfare of all his wives and childrens.